2014
DOI: 10.1105/tpc.114.130641
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Gene Expression Analysis by Reverse Transcription-Quantitative PCR: Reporting and Minimizing the Uncertainty in Data Accuracy  

Abstract: Reverse transcription-quantitative PCR (RT-qPCR) has been widely adopted to measure differences in mRNA levels; however, biological and technical variation strongly affects the accuracy of the reported differences. RT-qPCR specialists have warned that, unless researchers minimize this variability, they may report inaccurate differences and draw incorrect biological conclusions. The Minimum Information for Publication of Quantitative Real-Time PCR Experiments (MIQE) guidelines describe procedures for conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 24 publications
1
101
0
2
Order By: Relevance
“…Remans et al (2014), three internal genes of eggplants including GAPDH (F: CCGCTCCTAGCAAAGATGCC, R: ACCCTCCA-CAATGCCAAACC), 18sRNA (F: TAGTTGGACTTTGGGATGGC, R: AGAGCGTAGGCTTGCTTTGA), and Cyclophilin (F: AGGGTTCATGTGT-CAAGGAGGTGA, R: TCCAACAGCCTCGGCCTTCTTAAT) were used as internal controls. Quantitative PCR was performed with an Applied Biosystems 7300 Real Time PCR System (Applied Biosystems, Foster City, California, USA).…”
mentioning
confidence: 99%
“…Remans et al (2014), three internal genes of eggplants including GAPDH (F: CCGCTCCTAGCAAAGATGCC, R: ACCCTCCA-CAATGCCAAACC), 18sRNA (F: TAGTTGGACTTTGGGATGGC, R: AGAGCGTAGGCTTGCTTTGA), and Cyclophilin (F: AGGGTTCATGTGT-CAAGGAGGTGA, R: TCCAACAGCCTCGGCCTTCTTAAT) were used as internal controls. Quantitative PCR was performed with an Applied Biosystems 7300 Real Time PCR System (Applied Biosystems, Foster City, California, USA).…”
mentioning
confidence: 99%
“…Based on the available sequences of C. glauca database (Hocher et al 2011), a set of ten candidate genes were selected, comprising several commonly used reference genes in plants (Remans et al 2014;Goulao et al 2012;Gutierrez et al 2008): ubiquitin (Ubi); adenine phosphoribosyltransferase (Apt); elongation factor 1α (Ef-1); tubulin (Tub); eukaryotic initiation factor 4α (Elf-4A); glyceraldehydes 3-phosphate dehydrogenase (GAPDH); 40S ribosomal protein (S23); clathrin adaptor complexes subunit (Ap47); actin (Act); serine/threonine protein phosphatase (PP2A) ( Table 1). For each gene, specific primers were designed using the Primer3 software (Rozen and Skaletsky 2000), according to the following parameters: melting temperature (Tm) of 58-62°C, GC content of 45-55 % and length of the primers between 20 and 22 bp.…”
Section: Reference Gene Selection and Primer Designmentioning
confidence: 99%
“…One of the most assertive approaches used for such studies is the analysis of gene expression by quantitative real-time PCR (qRT-PCR) due to its high sensitivity, specificity and ability to accurately quantify the relative transcript numbers over an ample dynamic range in different organisms, tissues and environmental conditions (Valasek and Repa 2005;Bustin and Mueller 2005). However, qRT-PCR specialists have warned that, unless researchers minimize technical and biological variation, inaccurate differences might be reported and incorrect biological conclusions will be drawn (Remans et al 2014;Bennett et al 2015). Correct technical procedures imply an accurate selection and validation of reference genes for data normalization and thus for a valid analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As other studies have shown, RT-qPCR analyses are very sensitive and require several efforts to minimize variability at the technical and biological levels (REMANS et al, 2014). present a summary of the steps considered for the analyses of this work, and that could be applied to other genes and plant species (Table 5.1).…”
Section: Discussionmentioning
confidence: 99%